The Domestic Wastewater Treatment Installation's Performance Study of Technical Aspects in Cahaya Abadi Housing, Palembang City - Bachri, Jito; Handoko, Chanel Tri; Jimmyanto, Hendrik; Susanti, Susi (ENVIRO: Journal of Tropical Environmental Research, 2023)
The comprehensive treatment of rural water pollution was pioneered by developed countries, and many nations now have a variety of sewage treatment facilities and process technology that are suitable for their rural features. Domestic sewage is handled differently at sewage treatment facilities in cities than it is in rural areas. Its distributed drainage sites make it difficult to collect. The Indonesian government is implementing domestic wastewater treatment (DWWT) to reduce water pollution in areas without separate residential waste processing. The results of this analysis show that an extensive amount of maintenance is needed to ensure that the DWWT and its distribution system run as efficiently as possible. The Cahaya Abadi Housing in Sri Mulya Village, Sematang Borang District, Palembang City, is where the study is being carried out. DWWT Cahaya Abadi processes domestic liquid waste from household activities, although even though the facility has room for 169 dwellings, only 31 homes use it. As a result, capacity is not being used. The results of identifying the technical factors show that the use of pumps results in differences in flow discharge that affect the outcomes of the DWWT output. The extremely rapid pump that is being used has an impact on the processing process and the current detention time.